Are Artificial Intelligence Chatbots Fast and Safe For Patients and Dentists? - Bilge, Kübra; Ipek, Irem; Aşar, Enes Mustafa (My University, 2025)
Objective: The aim of this study was to evaluate the accuracy and response time of three different artificial intelligence (AI) chatbots' answers to questions frequently asked by clinicians and patients. Materials and Methods: In this study, dentists specialized in Oral and Maxillofacial Surgery, Pediatric Dentistry, Restorative Dentistry, Endodontics, Orthodontics, Oral and Maxillofacial Radiology, Periodontology and Prosthodontics were asked to prepare a total of 80 questions (n=10). The questions were multiple choice questions requiring text-based answers. 64 questions frequently asked by patients and 16 questions were selected from the WebMD website. Each question was asked once by one of the authors to each large language model (LLM). The answer to each branch's question was evaluated by two experienced experts who specialize in their field. LLM's answers were graded on Likert scale of 1 (minimum) to 5 (maximum) points according to the scoring key. Results: When the answers given by 3 LLMs in all branches of dentistry were evaluated in terms of time, Bing gave the latest answer, while ChatGPT gave the fastest answer and LLMs are evaluated in terms of points; no statistically significant difference was found (p<0.001). Conclusion: Considering the answers AI chatbots provide to dentistry-related questions and questions frequently asked by patients, they are likely to have a significant impact on various aspects of dentistry in the near future.
Keywords: Dentistry; Artificial intelligence; ChatGPT; chatbots; gemini; bing